Direct interaction of lignin and lignin peroxidase from Phanerochaete chrysosporium - Johjima, Toru (The National Academy of Sciences, 1999)
Binding properties of lignin peroxidase (LiP) from the basidiomycete Phanerochaete chrysosporium against a synthetic lignin (dehydrogenated polymerizate, DHP) were studied with a resonant mirror biosensor. Among several ligninolytic enzymes, only LiP specifically binds to DHP. Kinetic analysis revealed that the binding was reversible, and that the dissociation equilibrium constant was 330 μM. The LiP–DHP interaction was controlled by the ionization group with a pK(a) of 5.3, strongly suggesting that a specific amino acid residue plays a role in lignin binding. A one-electron transfer from DHP to oxidized intermediates LiP compounds I and II (LiPI and LiPII) was characterized by using a stopped-flow technique, showing that binding interactions of DHP with LiPI and LiPII led to saturation kinetics. The dissociation equilibrium constants for LiPI–DHP and LiPII–DHP interactions were calculated to be 350 and 250 μM, and the first-order rate constants for electron transfer from DHP to LiPI and to LiPII were calculated to be 46 and 16 s(−1), respectively. These kinetic and spectral studies strongly suggest that LiP is capable of oxidizing lignin directly at the protein surface by a long-range electron transfer process. A close look at the crystal structure suggested that LiP possesses His-239 as a possible lignin-binding site on the surface, which is linked to Asp-238. This Asp residue is hydrogen-bonded to the proximal His-176. This His–Asp⋅⋅⋅proximal-His motif would be a possible electron transfer route to oxidize polymeric lignin.